Tinjauan Sosial Pertambangan Minyak Ilegal di Kabupaten Musi Rawas Utara Tahun 2023 - AR, Muhamad Habibullah (Hutanasyah : Jurnal Hukum Tata Negara, 2023)
There are at least 8,000 illegal oil wells managed by the community illegally, spread across several districts including Musi Banyuasin, Pali and Musi Rawas Utara which are more concerned that illegal wells have entered protected forest areas and restoration forests protected by the state. Illegal oil well mining that occurs in North Musi Rawas district comes from Belani Village, Rawas Ilir District and its surroundings, and some of the crude oil under the Pantai Village of Rupit District has been going on for the past few years. Law Number 22 of 2001 concerning Oil and Gas is prohibited from illegal oil mining. This research uses Empirical Juridical methods related to legal issues in practice or actual reality in the field. Empirical research is so that legal research methods that seek to see law in a real sense without any engineering occurring or can be said to see, examine how law works in society. The results concluded that the illegal oil miners in Belani village and Pantai village did not carry out oil mining according to the applicable procedures but residents did it in the traditional way. As a result of oil mining and refining, it continues at this time due to the lack of concern from the surrounding community to report this illegal mining incident to the authorities, in this case the Rupit Police Chief and Musi Rawas Utara Police Station. Another factor in oil mining and refining is still happening is the change in the pattern of society where previously oil palm and rubber farmers have now turned into illegal oil miners and refiners, they consider the income from mining to be greater than that of oil palm and rubber farmers.